Fuzzy Intrusion Detection Method and Zero-Knowledge Authentication for Internet of Things Networks - Elangovan Muniyandy, Iratus Glenn A. Cruz, Mansoor Farooq, Yeruva. Jaipalreddy, Rakesh Kumar, Vivek Kumar Pandey (International Journal of Intelligent Systems and Applications in Engineering, 2024)
One of the encouraging trends that has contributed to the exponential rise in human progress over the last decade is the Internet of Things (IoT). Interconnection of physical objects for the purpose of data exchange is the next frontier of the internet, known as the Internet of Things (IoT). Everything from household appliances to cars to buildings to animals is part of the Internet of Things (IoT). The Internet of Things (IoT) has become the de facto standard because to its many useful uses in business, medicine, agriculture, and other fields. The Internet of Things (IoT) integrates wireless, pervasive, and ubiquitous technology to solve problems. Things with sensors implanted in them and linked over the internet make it up. Data is collected and shared by these networked devices. Many applications rely on the monitoring and analysis of data originating from heterogeneous devices. Fuzzy logic is used in this study to create a new, lightweight intrusion detection system (IDS) for Internet of Things (IoT) applications based on the MQTT protocol. Using fuzzy variables, the IDS detects network irregularities. In conclusion, this study offers a fresh security framework to solve the problems with current algorithms in an Internet of Things setting. This study also provides an application layer security that smart environments may use to avoid DoS attacks